PERANCANGAN RESORT DI DANAU UBUR-UBUR MARIONA DENGAN PENDEKATAN ARSITEKTUR EKOWISATA - Demak, Nini A. Kiay; Nurhaliza Mandagi; Kaharu, Arlan (Universitas Bina Taruna Gorontalo, 2024)
The aim of this research is to create a resort building in the Mariona Jellyfish Lake area by implementing ecotourism architecture in the design. This study method uses descriptive analysis to determine field conditions, markets and tourist interests. Data collection was carried out through field surveys to obtain primary data, which included direct observation of site conditions, analysis of physical conditions and the environment around the site. The natural beauty of the Mariona Jellyfish Lake area and its surroundings should be enjoyed. However, there is no adequate cultivation in the area at present, so conditions remain natural and disorganized, which makes it impossible to enjoy the existing natural beauty comfortably. To achieve this, good processing is needed, namely creating a tourist spot to enjoy natural beauty, especially by utilizing the Mariona Jellyfish Lake to preserve the environment and preserve the life and health of local residents. Lack of knowledge about natural processing causes nature to become damaged and cannot be enjoyed by humans. Therefore, there needs to be a place where people can enjoy the beauty of nature while protecting it so that it can be enjoyed now and in the future. Because the location is far from the city, you cannot visit all the tourist attractions in one day, tourist attractions must be supported by the resort. Therefore, a resort must be built that provides various recreational and tourist facilities in addition to accommodation.